Alih Fungsi Lahan di Kawasan Pariwisata Nusa Penida - Nyoman Sudipa; Made Sudiana Mahendra; Wayan Sandi Adnyana; Ida Bagus Pujaastawa (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2020)
Nusa Penida is part of the Province of Bali which consists of three small islands, namely Nusa Penida Island, Nusa Lembongan and Nusa Ceningan within the administrative area of Nusa Penida District, Klungkung Regency. The development of tourism in Nusa Penida has increased access to physical development and supporting facilities for the region. The leap of development of tourism facilities began to be felt starting in 2005, namely on the islands of Nusa Lembongan and Nusa Ceningan. The development of massive tourism facilities took place in 2015 until 2019 since the 2014 Nusa Penida Festival was held. Many coastal and inland areas were built with tourism accommodation, which naturally led to land conversion and land depreciation. The purpose of this study was to determine land use change from 2003 to 2019 using the overlapping analysis method of Google maps and maps derived from quick bird imagery. Transfer of land functions in the Nusa Penida Region from 2003 to 2019 reached 164.84 ha or the rate of land use change that occurred in the Nusa Penida Region was 0.85%.